Om Grundtvigdebatten med svar til mine kritikere - Michelsen, William (Grundtvig-studier, 1992)
About the Grundtvig Debate, with Answers to my Critics By William Michelsen This article has been written from the general principle that a distinction must be made between ascertaining what Grundtvig wrote in poetry or prose, and the individual scholars’ personal (existential) attitudes to it, even though such attitudes will inevitably colour their mode of expression. The essential thing is to maintain the fundamentally objective attitude as crucial to research. Kim Arne Pedersen's » Hermeneutic Reflections« in » Grundtvig Studier«, 1991, on the articles in Grundtvig’s » Danne-Virke«, 1816-19, consist by and large in an excellent summary of my introductions to these articles. The English summary, however, claims that it was his intention to give »a new interpretation« of these articles. As a matter of fact, the main view in his interpretation is the same as that taken by Henning Høirup in his thesis » Grundtvig’s view of faith and cognition« from 1949, viz. that Grundtvig’s thinking is influenced by the philosophy which he had learned at the University of Copenhagen, and which mainly reflected Leibniz and Wolff, while not including Kant’s philosophy. - However, Kim Arne Pedersen claims himself that he is »fascinated« by the post-Kantian idealistic philosophy, thus siding with Grundtvig’s contemporaries.He is right, of course, that this is an existential question. I can only answer that as far as I myself am concerned. I do not consider it possible to combine pre-Kantian thinking with a post-Kantian philosophy of idealism. In fact, I do not believe it is at all possible to combine the Christian faith or a Christian view of life with an idealistic philosophy.I think I have learned this from Grundtvig whom I regard as the best guide I know, if - that is true - the development that he underwent through his lifetime is carefully followed. A religion which builds its truth on a philosophy of one kind or the other, is no genuine religion. It will collapse the moment this philosophy is contradicted by reality. In his » Prospect of the World Chronicle« 1817, Grundtvig writes about Leibniz referring to his Theodic.: »..Pillars may collapse, and what rests on them totters, when they are shaken; thus also a disciple of Leibniz nearly tore them down before they had been erected, and this disciple, who meant to surpass his master by tearing down the Church and building a world on the remains, was, as is well-known, nobody else but Christian Wolff from Breslau« (p.409).With these words in mind, it seems impossible to me to regard Grundtvig as only a pupil of Leibniz and Wolff, though his teacher in philosophy undeniably was. The only contemporary thinker that absorbed Grundtvig for a short time, was Schelling. Grundtvig’s relationship to him has been discussed in C.I. Scharling’s book » Grundtvig and Romanticism« (1947), which was reviewed by me in Grundtvig Studier 1948. The book is important because it definitely refutes the view claimed by Edvard Lehmann in 1931, viz. that Grundtvig was actually a pupil of Schelling, and thus a philosophical idealist. But, as does Grundtvig himself, Scharling points out that even after 1810 Grundtvig could give credit to Schelling where he found he was right.As a literary historian with the methodology of the history of ideas as the foundation for my work, I must of course record these essential prerequisites for Grundtvig’s thinking and writings. My overall approach is this: What was the peculiar character of Grundtvig’s work and thought? From such an approach it seems to me quite reasonable that in my discussion of the manuscript » Grenzen der Menschheit« I distinguish between what Grundtvig accepts in Schelling, and what as a Christian he must reject.Grundtvig’s relationship to Kant depends on what he has read from him, and when he read it. He does not enter into a philosophical critique of Kant, of whom he had shown unreserved recognition in » Brief View of the World Chronicle« 1812. He confines himself to proposing an alternative to Kant’s philosophy, which, it is true, is founded on pre-Kantian philosophy, but at the same time - and this is crucial - in the faith in the Almighty Trinity who allows of no selfcontradiction, and whose power Grundtvig thought, as late as 1817, could be demonstrated through the course of world history.As long as Grundtvig only knew Kant’s philosophy of religion, i.e., in 1812, he thought that the reservation implied in the title, » Die Religion innerhalb der Grenzen der blo.en Vernunft« was enough to ensure that faith did not succumb to reason. When, in 1815, he read » Die Kritik der reinen Vernunft« he understood that faith had succumbed to reason, that man’s limitation had been exceeded, and that the maxim of contradiction had been reduced to a rule of formal logic. That is why his evaluation of Kant, in the World Chronicle of 1817, turns out to be very different.The intention of my article in Grundtvig Studier 1991 about .The Way from Force to Freedom in Grundtvig’s Life and Writings. was not to contradict Kaj Thanings thesis » Man first... « (1963), as it is claimed in the » Reply«, preceeding the present article. My approach in that article was a different one from Thaning’s; hence the difference in the treatment of the same texts which anyone can see, and which it would be absurd of me to deny. We see the texts from different points of view, and that is why they look different.In the view of both Thaning and myself, the watershed in Grundtvig’s body of work is .Norse Mythology., 1832. What I have added is the essential explanation of why this is so, viz. that after becoming a clergyman in 1811, Grundtvig found himself compelled to dissociate himself from the view that had taken him back to a religious view of life in the first place, namely Norse mythology. Thaning is right in claiming that it was internal causes that led to the ruptures that occurred in Grundtvig’s development. But they were provoked by external circumstances. I am not just referring to his parents’ demands on him in 1810, but also to the demands of the State Church on anyone who is a clergyman.I agree with Thaning that the relation between human life and Christianity was the main problem in Grundtvig’s life. When one is a clergyman, this relation becomes a theological problem, which it does not necessarily have to be if one is not a clergyman. I would describe what happened in Grundtvig’s life in 1832 like this: » The scales fell from Grundtvig’s eyes when he decided to write his new Norse Mythology«. He now dared to write that book without being afraid of losing his Christianity in doing so. He was free and could freely accept becoming a vicar to a congregation that wanted him. He was free to describe Norse mythology as a language of symbols which lent itself to historical explanation and to poetical consideration, without, in so doing, making it into his religion. The essential thing, in my view, is that he had given up wanting to demonstrate the truth of Christianity by means of history. Christianity remains a faith which is inextricably bound up with the Mosaic-Christian view, which is therefore the »only divine, true, and eternal one«. This new attitude depends on his discovery that faith must be a free matter if it is to be honest and true at all.In my opinion, it is no weakness to admit the justification of other views than one’s own. It is a prerequisite for cooperation and team-work.